1992
DOI: 10.1001/archsurg.1992.01420100114020
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Biopsy Causing Peritoneal Seeding of a Carcinoid Tumor

Abstract: A rare complication of fine-needle aspiration biopsy (FNA) is needle tract seeding. Peritoneal seeding from FNA in the clinical setting is rarely reported. To our knowledge, this is the first case of peritoneal seeding of a neuroendocrine carcinoid tumor as a result of FNA. Peritoneal contamination and tumor seeding can occur with FNA and they probably do occur more often than is recognized clinically. Therefore, we caution against the use of FNA in the assessment of potentially curable intra-abdominal tumors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Biopsying renal cell carcinomas (papillary adenocarcinoma) and Wilm's tumors may also cause tumor growth along the needle tract (23, 26, 49). Needle tract seeding of hepatocellular carcinoma has been reported, as well as individual cases of carcinoid tumors (42) and liver metastases of colon cancer (63, 65). Malignant mesothelioma seeding to the thoracic wall is well established, and other thoracic tumors can also metastasize to the puncture site (10, 47).…”
Section: Complicationsmentioning
confidence: 99%
“…Biopsying renal cell carcinomas (papillary adenocarcinoma) and Wilm's tumors may also cause tumor growth along the needle tract (23, 26, 49). Needle tract seeding of hepatocellular carcinoma has been reported, as well as individual cases of carcinoid tumors (42) and liver metastases of colon cancer (63, 65). Malignant mesothelioma seeding to the thoracic wall is well established, and other thoracic tumors can also metastasize to the puncture site (10, 47).…”
Section: Complicationsmentioning
confidence: 99%
“…Review of an Italian multicenter study of ultrasonically guided fine‐needle abdominal biopsy showed a major complication rate of 0.18% 15 . However, several complications after FNA for pancreatic masses have been reported, including fatal necrotizing pancreatitis, 16 infection of the cystic neoplasm 17 and malignant seeding to the peritoneum 18,19 or needle tract 15,20 . Yasuda et al 21 reported a case of mucin‐producing pancreatic tumor in which mucus leaked into the abdominal cavity during pancreatoduodenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It increases further to 10% in colorectal malignancies (6). FNA can also cause transpleural spread of lung cancer (7), while intra-abdominal tumors like hepatocellular carcinoma (8) and carcinoid tumor (9) have been reported to spread through the peritoneal cavity. Even esophageal ultrasound-guided FNA of pancreatic adenocarcinomas (10) failed to prevent tract seeding.…”
Section: Needle Tract Seedingmentioning
confidence: 99%